ISSUES OF LEGAL MONITORING OF ANTI-CORRUPTION LEGISLATION (Journal of actual problems of jurisprudence, 2025)
Corruption is a problem on the way of development of the state and society. The task of the state is to reduce the negative impact of corruption on the development of the state and society. This article examines a number of issues related to combating corruption in Kazakhstan and foreign countries. The authors analyze the criminal and other legislation of the Republic of Kazakhstan and foreign countries in the field of combating corruption. Each state chooses its own way of combating corruption, much depends on the level of development of criminal and administrative legislation, the degree of involvement of society in the fight against corruption, the level of legal awareness of society and civil servants themselves. The legislation of foreign countries that successfully counteract corruption, international legal acts in the field of combating corruption are of great interest in terms of adopting successful experience, rethinking the domestic approach in formulating the conceptual apparatus, legal norms and approaches to combating corruption in criminal law and other legislation of the Republic of Kazakhstan.The object of the study- legislation in the field of criminal law and anti-corruption. Subject of research. Implementation of doctrinal monitoring of current legislation in the field of criminal law using the example of legislation on combating corruption in the context of the socio-economic Purpose of the study. The establishment of methodological foundations for the inclusion of the model of developed foreign states in the norms of criminal law of Kazakhstan on combating corruption.The importance of work. It consists in filling certain gaps in the field of criminal law and anti-corruption activities, the possibility of applying conclusions and proposals in legislative activities on improving the Criminal Code of the Republic of Kazakhstan.Keywords: anti-corruption, criminal law, criminal liability, punishment.